Electroacupuncture for blood pressure control in elderly hypertensive patients - Sang Ayu Ketut, Candrawati; Ni Komang Sukra Andini; Desak Made Ari Dwi Jayanti (KHD-Production, 2026)
Hypertension is a major global health problem and a leading risk factor for cardiovascular diseases, especially among the elderly, due to decreased vascular elasticity, increased peripheral resistance, and autonomic dysfunction. Despite pharmacological therapy, poor adherence and side effects highlight the need for complementary non-pharmacological interventions. Electroacupuncture has emerged as a potential therapy to support blood pressure control in elderly hypertensive patients. This study aimed to evaluate the effectiveness of electroacupuncture in reducing blood pressure among elderly patients with hypertension. A quantitative pre-experimental one-group pretest–posttest design was conducted on 20 elderly hypertensive patients. Electroacupuncture was applied to GV20, ExHN3, ExHN5, LI4, LI11, PC6, ST36, LR3, and KI3 points for 30 minutes per session over six sessions in three weeks. Blood pressure was measured before and after the intervention using a calibrated sphygmomanometer. Data analysis was performed using the Wilcoxon Signed Rank Test for systolic blood pressure and the Paired Sample T-Test for diastolic blood pressure with α = 0.05. Systolic blood pressure decreased significantly from 133.27 ±16.59 mmHg to 128.85 ±15.97 mmHg (p=0.011), while diastolic pressure decreased from 76.04 ±9.08 mmHg to 74.90 ±7.43 mmHg without statistical significance (p=0.240). Electroacupuncture is effective, safe, and economical in reducing systolic blood pressure in elderly hypertensive patients. It is recommended as a complementary therapy integrated with conventional management for holistic hypertension control and improving quality of life among the elderly.